Online robustness damage identification of dynamic response of high pile wharf under wave excitation. (1st April 2023) - Hu, Yan; Wang, Qi-ming; Zhu, Rui-hu; Li, Cheng-ming; Wang, Ning
Abstract: Damage identification based on dynamic response is an important nondestructive test method for pile foundation in high-pile wharf. Wave is a common excitation form of high-pile wharf. It is of great significance to use dynamic response under wave excitation to realize early and online damage identification. However, there are two noticeable problems in dynamic response under wave excitation: multi-type aliasing effect and narrowband effect, which leads to inaccuracy and instability in damage identification. Aiming at solving the aliasing effect, this paper constructs a new method to extract characteristic dynamic response under wave excitation based on empirical mode decomposition (EMD) and spectral characteristic analytical methods. The reliability and robustness of damage identification are improved by removing ineffective components of dynamic response. Further, considering the narrow-band effect and the weakness of the response, a novel online damage identification method based on the weighted non-parametric cumulative sum (WCUSUM) was constructed. The method uses the accumulation of model residuals to sensitively capture the changes of key components in dynamic response in order to realize early damage identification. The applicability and sensitivity of the method was verified by experimental model in wave flume under different damage conditions. The method proposed in this paper provides a new idea for the online damage identification of pile foundation based on wave excitation, and a new tool for the online damage identification of offshore marine structures during service. Highlights: Automatic extraction method of characteristic dynamic response under wave excitation based on empirical mode decomposition and spectrum characteristic test. An online method based on weighted nonparametric cumulative sum is proposed to enhance the characteristics of dynamic response signals and realize damage time localization by identifying characteristic signal change point. Discussions of parameter sensitivity, feasibility and effectiveness of the method based on the experimental model.